Paraplegia in Pregnancy A Case of Spinal Vascular Malformation With Klippel-Trenaunay Syndrome - Demir, Caner Feyzi; Yildiz, Mustafa; Ozdemir, Hasan; Kapan, Oktay; Bozgeyik, Zulkif; Berilgen, Said; Erol, Fatih Serhat (Lippincott Williams & Wilkins, 2012)
Study Design. A case report. Objective. To present improvement of paraplegia due to spinal vascular malformation after delivery with no intervention. Summary of Background Data. Pregnancy has been reported rarely in patients with Klippel-Trenaunay syndrome (KTS). A combined case of spinal arteriovenous malformations (AVMs) within KTS has not been reported before. Methods. A case report of KTS with paraplegia is presented and the pertinent literature is then reviewed. Results. A pregnant woman who was diagnosed with KTS in childhood presented with newly developed paraplegia due to spinal AVMs. Magnetic resonance image showed a vascular malformation at the T9-T12 levels without evidence of spinal cord hemorrhage. Diagnostic angiography that was performed after delivery revealed a high-flow arteriovenous fistula with AVM. Conclusion. Pregnancy complicated by paraplegia is thought to be secondary to venous engorgement and to the resulting spinal cord ischemia in this case. Her neurological symptoms and signs gradually improved over the few days after cesarean delivery.
Keywords: Klippel-Trenaunay syndrome; spinal vascular malformation; pregnancy